An Analytic Study on the Enhancement of Heat Transfer with Nanofluid - Bhuvaneswari SUBRAMANIAN; Elatharasan GOVINDARAJ; Mukesh Kumar PERIYASAMY CHOKKAYEE AMMAL (Medžiagotyra)
The article studies the problem of boundary layer fluid flow for two dimensional steady and incompressible    hybrid nanofluids over the nonlinear stretching surface. The problem is analysed for the distribution of velocity, temperature, and concentration profile influenced by the parameters taken for study. The pertinent parameters analysed in the boundary value problem are magnetic, non-linear stretching parameter, Prandtl number, radiation, Brownian, thermophoresis. The governing sets of PDE’s are converted to a set of ODES using the similarity transformations. The numerical results are obtained by RK algorithm techniques. The study portrays the results for skin friction and Nusselt number for varying the parametric values. The interpretation of results is done graphically and in tabular format. The detailed parametric study is explored for the enhancement of heat transfer, the influence of the parameters on velocity, temperature, and volume fraction of the nanofluid, skin friction coefficient, and Nusselt number. The wide applications of the problem taken for the study where the control of complex parametric influence in heat transfer is applied in the field of energy recovery, biomedical, and industrial systems in the present global scenario.